Protecting Vulnerable Children from Uninsured Risks: Adapting Conditional Cash Transfer Programs to Provide Broader Safety Nets - Alain de Janvry; Elisabeth Sadoulet; Renos Vakis (Fondation pour les études et recherches sur le développement international (FERDI), 2008)
Conditional cash transfer (CCT) programs have proved to be effective in inducing chronic poor households to invest in the human capital of their children while helping reduce poverty. They have also protected child human capital from the shocks that affect these households. In this paper, we argue that many non-poor households exposed to uninsured shocks have to use children as risk coping instruments, with the risk of creating long term irreversibilities in child human capital development. We review recent experiences to explore how CCT programs could be designed to serve as safety nets for the vulnerable non-poor when hit by a shock. This would require a number of modifications to the way rules of operation of CCT programs are currently designed.
Keywords: O16; G22; I3; 330